Ensino de pais sociais: contribuições da análise do comportamento no acolhimento institucional da pessoa com deficiência intelectual - Mendes, Jeyverson Ferreira (2019)
Previous studies have presented elements that corroborate the importance of a Behavior Analysis Training Program for parents and caregivers. Despite the advances obtained, limitations were found mainly to affirm what would be the components of the treatment program, of which the positive effects in the changes of parental styles would be function. Considering this difficulty, the present research aimed to investigate whether a program of teaching of parental skills, theoretically based on behavior analysis, would produce changes in the behavioral repertoire of the participants and to which variables they were due. For this, a multiple baseline experimental design was used between behaviors. The procedure involved 3 phases: 1. Baseline Phase, 2. Intervention Phase and 3. Generalization Test Phase. The teaching program was composed of nine stages, divided between teaching by instruction, teaching using videofeedback and teaching using role-play, in order to positively reinforce appropriate behaviors, not punish and extinguish inappropriate of people with intellectual disabilities residing in an institution philanthropic center of the city of Belo Horizonte. The results showed that, after teaching, all participants were able to practice the procedures taught. There was an increase in the frequency of adequate reinforcing responses, reduction of punishment responses and reasonable use of the extinguishing procedure. The component teaching by instruction changed the participants' performance poorly, while videofeedback and role-play were the components that produced significant changes, the latter being a little more effective. The generalization test with participants who reached this phase (P1 and P2) showed that both reinforced, in interaction with the target users, other behaviors that were not explicitly taught and also reinforced appropriate behaviors of the other users